Advancements in facial implantology: a review of hydroxyapatite applications and outcomes - Kauke-Navarro, Martin; Knoedler, Leonard; Knoedler, Samuel; Safi, Ali Farid (Frontiers in Surgery, 2024)
The search for an ideal bone substitute in reconstructive surgery has led to the exploration of various materials, with hydroxyapatite (HaP) emerging as a promising candidate due to its biocompatibility, osteoconductive properties, and structural similarity to human bone. Despite its potential, there is a paucity of data on the long-term safety and efficacy of HaP in facial skeletal reconstruction and augmentation.We conducted a systematic review following PRISMA 2020 guidelines, searching PubMed/MEDLINE, Google Scholar, CENTRAL, and Web of Science databases for studies on hydroxyapatite facial implants in reconstruction and augmentation.Our search yielded 12 studies that met our inclusion criteria, encompassing 74 patients treated with HaP implants for various indications including facial fractures/defects, aesthetic facial balancing, and after tumor resection. The studies reported on outcomes such as implant integration, complications, aesthetic results, and patient satisfaction, with a general trend indicating positive outcomes for the use of HaP in facial reconstruction.Hydroxyapatite appears to be a viable and effective material for facial skeletal reconstruction and augmentation, offering benefits in terms of biocompatibility, osteoconductivity, and patient outcomes. However, limitations such as low mechanical strength and the need for further research on long-term safety and efficacy were identified. This review underscores the potential of HaP in craniofacial surgery while highlighting areas for future investigation.